Depresión postparto y su influencia en el núcleo familiar - Guerra Rivas, Genesis Ariana (2020)
The present research project was carried out at the Hospital Básico Arias, in Babahoyo city, to a 28-year-old woman with a moderate depressive disorder with onset in peripartum meeting the diagnostic criteria of the diagnostic manual DSM 5 for came to this diagnosis, the patient was given some psychometric tests which were Beck's depression inventory, Hamilton's anxiety scale and to evaluate the five basic functions of the family was the APGAR questionnaire. This case study aims to know how postpartum depression negatively influences the family nucleus causing discords, fights and quarrels in the home, it is also proven that postpartum depression not only happens after childbirth alsodevelops during pregnancy, corrodes in the same way that this mood disorder not only affects teenage mothers.